The dynamics of inter-organizational cooperation in Economic Interest Groups: Case of EIG TARGANINE in Morocco (International Journal of Scientific Research and Management (IJSRM), 2022)
Inter-organizational cooperation has become a major challenge for the development of organizations. Inter-organizational relations are enormously successful in terms of cooperation, especially when talking about Social and Solidarity Economy (SSE) companies. Today, several forms of cooperation appeared in Morocco with the creation of groups, unions, networks and federations. Through this paper, we study the dynamics of inter-organizational cooperation and its contribution to the economic and social development of an Economic Interest Grouping (EIG) of women’s cooperatives in Argan. We proceed for our analysis according to the dialectical approach as it was adopted by Dameron (2001, 2002), via the study of the cooperation relations of the EIG TARGANINE, based on a qualitative approach carried out by semi-structured interviews carried out with the president of the EIG and the leaders of the member cooperatives. Keywords Cooperation, Inter-organizational relations, EIG, Cooperative, Economic and social development.